Spatial Analysis of Dengue Hemorrhagic Fever in The Endemic Area of Magetan - Santosa, Budi Joko; Saadah, Nurlailis; Sumaningsih, Rahayu; Ngestiningrum, Ayesha Hendriana (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Dengue Hemorrhagic Fever was still a public health problem, the rapid distribution and the opportunity to cause death gives a frightening impression, therefore important to know the spread and characteristics its. Samples this study of all patients diagnosed with DHF was recorded in Candirejo Public Health Center from 2015-2017, that it is one of endemic areas in Magetan district, and analysis characteristic spatial. There were always cases of DHF in Baron villages, 3, 4 and 3 cases respectively with clustered locations, two years in a row always there, and most common case in January and February. The rainy season and temperature in this area support the proliferation of dengue vector breeding. Age of 56% patients is 6-17 years old, youngest age 0,5 and oldest 69 years old, and patients 59.65% is women, this indicates women are more at risk. Noted there was the number of platelet count recorded at below the normal level. Recommended surveillance, and community empowerment through clean and healthy behavior. Keywords: Spatial analysis, DHF, Place, Time, Person